2017
DOI: 10.1074/jbc.m117.806687
|View full text |Cite
|
Sign up to set email alerts
|

Functional defects in Clostridium difficile TcdB toxin uptake identify CSPG4 receptor-binding determinants

Abstract: is a major nosocomial pathogen that produces two exotoxins, TcdA and TcdB, with TcdB thought to be the primary determinant in human disease. TcdA and TcdB are large, multidomain proteins, each harboring a cytotoxic glucosyltransferase domain that is delivered into the cytosol from endosomes via a translocation domain after receptor-mediated endocytosis of toxins from the cell surface. Although there are currently no known host cell receptors for TcdA, three cell-surface receptors for TcdB have been identified:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 33 publications
2
60
0
Order By: Relevance
“…As shown by Manse & Baldwin, , PVRL3 interacts with the region of amino acids 1372–1493 within TcdB. Recent data show that CSPG4 binding also happens within the region of amino acids 1810–1850 (Gupta et al, ). As reported earlier, the combined repetitive oligopeptide (CROP)‐deleted TcdB (TcdB 1‐1852) is less potent than full‐length TcdB with respect to cell rounding (Olling et al, ).…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…As shown by Manse & Baldwin, , PVRL3 interacts with the region of amino acids 1372–1493 within TcdB. Recent data show that CSPG4 binding also happens within the region of amino acids 1810–1850 (Gupta et al, ). As reported earlier, the combined repetitive oligopeptide (CROP)‐deleted TcdB (TcdB 1‐1852) is less potent than full‐length TcdB with respect to cell rounding (Olling et al, ).…”
Section: Resultsmentioning
confidence: 85%
“…The alignment illustrates that (a) the GTD of TcdB 1470 and TcdB R9385 are almost identical, except three amino acid residues and (b) the trunk of TcdB R20291 and TcdB R9385 are also considered as identical except for 12 amino acid residues, all within the cysteine protease domain. If the most abundant receptor in target cells is deleted, a concentration of intracellular toxin sufficient to induce ECD might not be show that CSPG4 binding also happens within the region of amino acids 1810-1850 (Gupta et al, 2017). As reported earlier, the combined repetitive oligopeptide (CROP)-deleted TcdB (TcdB 1-1852) is less potent than full-length TcdB with respect to cell rounding (Olling et al, 2011).…”
Section: Translocation and Glucosylation Characteristics Account Fomentioning
confidence: 95%
“…2B). TpeL showed low toxicity and TcdA and TcdB were several orders of magnitude less toxic to HULECs than what is reported for other cell types (16,17). Remarkably, the GI50 of TcsL was ~50 fM, suggesting that only ~200 toxin molecules/cell are lethal to HULECs.…”
mentioning
confidence: 69%
“…Data from two studies (27,28) support the idea that TcdB binds CSPG4 in a region found within amino acids 1831 to 2366, which would be carboxy terminal to the region from amino acids 1769 to 1787. Using a combination of pulldown experiments and antibody-based blocking, Gupta and colleagues further narrowed the region of CSPG4 binding and found that it likely occurs within a region between residues 1824 and 1900 (29). This region is carboxy terminal to amino acids 1769 to 1787 in TcdB.…”
Section: Discussionmentioning
confidence: 99%